2004
DOI: 10.1007/s00464-003-9157-y
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic assessment of the static stress confronted by surgeons during laparoscopic cholecystectomy

Abstract: It was proven that surgeons are confronted by significant static burden during LC. The software used was able to evaluate objectively the static posture of the surgeon during series of LC. Results also confirmed that the position of monitors significantly influences the surgeon's posture. Best setups for the whole team can be achieved by adjustable multiple monitor systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 12 publications
1
38
0
4
Order By: Relevance
“…The side-standing position was associated with increased upper-arm flexion and abduction, shoulder elevation, neck flexion, and twisting. As was the case in a prior study [27], increases in trunk side-bending and flexion were confirmed. It is often assumed that laparoscopy is associated with greater wrist Fig.…”
Section: Discussionsupporting
confidence: 75%
“…The side-standing position was associated with increased upper-arm flexion and abduction, shoulder elevation, neck flexion, and twisting. As was the case in a prior study [27], increases in trunk side-bending and flexion were confirmed. It is often assumed that laparoscopy is associated with greater wrist Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Complaints concerning the neck and back can be caused by an uncomfortable and static posture in relation to the position of the monitor. Studies examining the most comfortable posture advise a viewing direction straight ahead and at a slightly downward angle [9,12,20]. In this monitor configuration, the working posture is the most neutral.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this positioning, the line of vision is diverted away from the line of action, creating an awkward posture including rotation of the spine, extension of the neck, and elevation of the upper extremities. This causes musculoskeletal complaints and possibly compromises surgical task performance [9][10][11][12].…”
mentioning
confidence: 99%
“…The unusual posture of upper limbs combined with the weak mechanical efficiency (friction) in the opening mechanism of instruments are reported to increase muscles recruitment. This overall lack of ergonomics in laparoscopy is at the source of pain and feeling of discomfort [2], [3], [6]. Most of these aches are due to the increase of muscular efforts in the upper limb.…”
Section: Introductionmentioning
confidence: 99%
“…Several reasons are pointed out: 2D monoscopic vision on screen, indirect vision of hands and unnatural line of sight, inversion and variable scaling of motions, reduced intra-abdominal mobility due to the fulcrum effect of the small incisions [1]- [3].…”
Section: Introductionmentioning
confidence: 99%